Adaptation of cognitive behaviour therapy in childhood obsessive-compulsive disorder: a case study - Sampurna Chakraborty; Susmita Halder (Open Journal of Psychiatry and Allied Sciences, 2020)
Cognitive behaviour therapy (CBT) has been proved to be one of the most well-researched and effective therapy. It has been found effective in many clinical conditions in children and adolescents as well. Application of therapeutic processes gets complicated by the facts that childhood and adolescent problems do not come in neat packages and tend to overlap and/or coexist. For instance, there is much overlap among clinical problems like anxiety, depression, behavioural problems, and between reading and writing difficulties, and attention and hyperactivity. Many behavioural and emotional disturbances in children are also associated with specific medical conditions. The relationship between physical and/or medical conditions and emotional and behavioural disorders in children and adolescent has been documented in various studies. This demands attention to the therapeutic intervention to the childhood problems with greater monitoring and modulation. Use of CBT in childhood and adolescent problems for efficiency and convenience may be grouped into externalising and internalising disorders, and the management techniques may be formulated and tailored to meet the two opposing dimensions. In this case study, index client was an eight years old girl who presented with compulsive behaviour along with anxiety and fear, and the application of CBT techniques, its adaptability and efficacy in this case of obsessive-compulsive disorder (OCD), with specific phobia would be discussed.